Circadian hormone secretion of enteroendocrine cells: implication on pregnancy status - Homeida, Abdelgadir M.; Homeida, Mohamed A.; Al-Suhaimi, Ebtesam A. (Frontiers in Endocrinology, 2023)
Timing of food intake is key cue for circadian rhythms in human and animals. In response to feed intake many gut hormones named incretin are produced by intestinal enteroendocrine cells in a circadian rhythm that stimulate insulin secretion, regulation of bodyweight and energy expenditure. Pregnancy is associated with expansion of β-cells, risk of gestational diabetes mellitus and overweight. Timing of food intake is a good approach to address metabolic complications during pregnancy. The current review focuses on the circadian rhythms and biological actions of enteroendocrine hormones and their association to pregnancy status, specifically topics like food intake and gut circadian rhythms, circadian secretion of enteroendocrine peptides, and their effects during pregnancy shall be addressed.